FREQUENCY OF GLUCOSE 6 PHOSPHATE DEHYDROGENASE DEFICIENCY AND RELATED HEMOLYTIC ANEMIA IN RIYADH, SAUDI ARABIA - Gandapur, A. S. Khan; Qureshi, Fayyaz; Mustafa, Ghulam; Baksh, Sattar; Ramzan, M.; Khan, Masood A. (Journal of Ayub Medical College Abbottabad, 2002)
Background: Glucose 6 Phosphate dehydrogenase deficiency is present in over 400 million people world wide. It is more common iin tropical and subtropical countries and is one of the important causes of hemolytic anemia and neonatal jaundice. We studied the frequency of glucose-6-phosphate dehydrogenase deficiency and associated complications in Central Region (Riyadh) of Saudi Arabia. Methods: A total of 1740 subjects referred by Ministry of Interior and different hospitals in Riyadh were investigated for glucose-6-phosphate dehydrogenase deficiency. Glucose 6 phosphate dehydrogenase activity was determined by a screening test described by Beutler. Results: Out of these, 106 (6.09%) subjects were deficient. The subjects were divided into marriage and hospital groups. In marriage group deficiency was 4.1% while in hospital group it was 13.3%. In 54 glucose-6-phosphate dehydrogenase deficient patients red blood cell count and haemoglobin levels were determined to see the degree of anaemia. Sixty one percent (61%) had anaemia. In hospital patients 8% patients had severe anaemia while in marriage group no patients had severe anaemia. However mild anaemia was seen in 25% subjects in marriage group. Conclusions: In conclusion the study indicates that glucose-6-phosphate dehydrogenase deficiency is common in the central region of Saudi Arabia and a lot of patients present with haemolytic episodes. The haemolytic crisis however is not related to the intake of fava beans. The type of variant causing anaemia and suggestions for prevention in marriage group are outlined. Key words: glucose-6-phosphate dehydrogenase, deficiency, anaemia, marriage